Содержание образования бакалавров – проблемы и решения: компетентностный подход - Nabiev V. S. (Scientific studies and modern education, 2017)
The author discusses the founding of the substantive content of activity of participants of educational process in higher school.
Keywords: компетентностный подход; образовательный процесс; educational process; Competence approach